A Broken Leg in the Year 1350: Treatment and Prognosis - Wiel van der Mark (EXARC Journal)
Analysing and reconstructing medical treatments: unique approach to heritage interpretation through research and re-enactment. It is the year 1350 in Gravendam (the medieval town of the archaeological open-air museum, (AOAM) Archeon, in the Netherlands). Master Roelof, a wood-and-bone processor, lies unconscious on the stone floor. Shortly before this, he had been climbing the ladder to the attic to grab a log of wood, but it slipped from under him and he ended on the floor. Roelof fainted from the pain, and his leg now lay at a strange angle (See Figure 1). His wife Mette sees that it is not right and hastens to the barber-surgeon for help immediately (See Figure 2). Accidents did happen in the Middle Ages. What could the barber-surgeon have done for Roelof’s broken upper leg? Could he have treated the fracture and the possible complications from this injury? What were Roelof’s chances of survival? In this first article about medical medieval treatments in Archeon, the treatment of this medical problem will be described and interpreted.